PROPUESTA DE MEJORAMIENTO DE LA CARGA TRIBUTARIA EN EL SECTOR ECONÓMICO COMERCIAL DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA - Correa Pardo, Edilma Fernanda (2016)
The production of any territorial sector is an economic indicator that characterizes the development of that region, as in the case of the canton of Catamayo in the province of Loja, where the commercial economic activity is a commercial movement that generates resources where all its members are part of the tax sharing according to the rules in force as taxpayers. Tax collection is a public function managed by the State through the respective state agencies in order to apply taxes where every citizen must comply with these mandatory provisions aimed at financing the State Budget, but at the same time citizens expect an efficient redistribution of wealth that contributes to economic and social welfare of the country. This research topic was conducted in order to diagnose the tax burden on the business sector of the canton of Catamayo and establish a proposed improvement to ease the liege weight for which taxpayers were classified into three kinds: those who belong to General regime known as OTHERS, the registered in the Simplified Tax Regime named RISE and those with additional tax obligations named SPECIAL. The methodology used for the proposed improvement consists of an analysis of tax collecting by economic sectors in the South Regional (Loja-Zamora) period January-November 2013 as well as by cantons of the province of Loja and finally by economic sectors of the Canton of Catamayo period January-September 2014 respectively, the data 5 confirmed a significant level of participation in the tax contribution of the business sector in the southern region and the canton. For the calculation of the tax burden was used the mathematical relationship of the Gross Domestic Product of the canton with the proceeds of certain financial obligations as SRI taxes, import duties, taxes, social security contributions and the employee profit method which allowed to extract the percentage of the actual tax burden of 7.36% vs. the traditional 2.88% which determines the IRS through collections that they compete only against the gross value added or GDP of the canton. Faced with these two percentage indicators it is conclude that the real tax burden on the commercial working class of canton is high compared to the traditional with an increase of 4.48 percentage points (pp), tax burden resulting in a merchant uninterested behavior in voluntarily comply with their tax obligations the same as disinterest to continue their productive business which justifies establishing improvement measures to alleviate the tax burden in this market sector catamayense considering that trade is a fundamental pillar in the economic development of this valley.